ANALISIS PROSES REKAMAN MUSIK DENGAN METODE DIGITAL DI KM STUDIO PONTIANAK - Richardson, Bill; Sanulita, Henny; Silaban, Christianly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by audio quality problem using music from video recordings in dance performances at campus of Dance and Music Education Program of FKIP University Tanjungpura. There are still many who use audio from live music video recordings for music in the dance show. This is the underlying interest of researchers to conduct research on the analysis of the recording process with digital methods in KM Studio Pontianak. This research uses descriptive research method with qualitative form using survey study with job survey type or job (Jobs Survey). This study was conducted in six stages based on the stages in the recording process and the analysis of the recording. The analysis of the recording shows the objectivity of the exposure of the frequency and its range in the stereo space and subjectivity based on the opinion of every resource who listened to the recording in this study.Keywords: Process, Recording, Music, Method, Digital